Penggunaan Cerucuk Kayu Dalam Menahan Deformasi Jalan (Studi Kasus: Ruas Simpang Tiga Jalan Nasional Pulang Pisau – Desa Belanti Siam Kabupaten Pulang Pisau STA 5+150) - Dimas Ardianto (Jurnal Serambi Engineering, 2025)
Road deformation at the Pulang Pisau National Road Intersection—Belanti Siam Village STA 5+150 is caused by instability of soft soil with low bearing capacity, disrupting transportation and the local economy. This study calculates the existing safety factor (SF) without reinforcement, designs reinforcement with galam wood studs, and evaluates its effectiveness. The Bishop method is used to calculate the SF, while Mochtar's (2000) theory is used to calculate the flexural strength and horizontal force of the studs. The results show an initial SF value of 1.0022, almost critical. The 4-meter-long, 10-cm-diameter galam studs can withstand lateral forces of up to 759.4 kg. To increase the SF to a minimum of 1.5, 13-14 studs per meter are required. After installation, the SF increases to 1.5283, indicating significant improvement in slope stability. Vertical stud installation with a 30 cm spacing and wet conditions are recommended to maintain the durability of the wood. Galam studs have proven to be effective and economical for reinforcing roads on soft soils, as well as environmentally friendly. This study provides technical guidance for road reinforcement using galam wood blocks.